Extrahepatic malignant neoplasms after liver transplantation: the experience of a single transplant center - O. A. Gerasimova; V. V. Borovik; F. K. Zherebtsov; D. A. Granov (Вестник трансплантологии и искусственных органов)
Objective: to evaluate the incidence of de novo malignant neoplasms (MN) after liver transplantation (LT) and compare with indicators among the general Russian population. Materials and methods. The study included 182 patients who had at least a 6-month follow-up period after LT and had no extrahepatic malignancies before LT. All data were analyzed retrospectively. Statistical processing of the results was carried out using the Statistica program for Windows v.10. Results. MN incidence was 5.5% (10 of 182 patients). The average period from transplantation to diagnosis of de novo neoplasm was 47.8 months (8 to 144 months). The patients were 3 men and 7 women. Types of de novo tumors included digestive system tumor (2 out of 10), hematologic malignant tumor (3 out of 10), skin cancer – melanoma (1 out of 10), urologic cancer (1 out of 10), gynecological (2 out of 10) and base of tongue cancer (1 out of 10). Five patients (50.0%) died, mortality was higher than in other LT patients (Z = –2.6; p = 0.009). The average follow-up period after detection of neoplasms was 18.8 months. Incidence of malignant neoplasms following LT was 10 times higher than among the general Russian population. No significant differences were found in the incidence of late acute rejection between 10 patients with MN and other 172 patients (Z = 0.18, p = 0.8). Among surviving patients, 2 patients with lymphomas received tacrolimus immunosuppression monotherapy, while 3 had everolimus-based immunosuppression. Conclusion. Incidence of de novo extrahepatic malignancies after LT is significantly higher than in the general population. To reduce the incidence of neoplasms in the future, patients should undergo regular screening, proliferative signal blockers should be prescribed, although their effectiveness requires further research.